Removal of MgO from the Chrome Cake Produced by Enzymatic Hydrolysis of Chrome Shavings - MOKREJS, P.; HRNCIRIK, J.; JANACOVA, D.; MLADEK, M.; LANGMAIER, F.; KOLOMAZNIK, K.; VASEK, V.; DVORACKOVA, M. (Asian Journal of Chemistry, 2010)
The tanning industry processes raw hides and converts them into leather, producing considerable quantities of solid and liquid by-products. The solid tanned by-products contain chromium and by-product liquors contain residual chromium. In order to prevent loss of protein material and chrome compounds, technologies were developed for recycling liquid and solid by-products. Recycling solid by-products is being successfully realized through enzymatic hydrolysis. The chrome cake remains an issue as it contains MgO which was used as a promoter in hydrolysis of chrometanned solid by-products. High content of MgO in the chrome cake complicates its further use. This presents work addresses the possibility of isolating magnesium, present as hydroxide, from the chrome cake using by-product (spent) tanning liquor. Results showed that it is possible to achieve magnesium removal efficiency up to 70 %.